2018
DOI: 10.4103/ijmr.ijmr_80_18
|View full text |Cite
|
Sign up to set email alerts
|

Setting research priorities in smokeless tobacco control: A retrospective review

Abstract: Background & objectives:Smokeless tobacco (SLT) has become a global menace; India being one of the high-burden countries contributes about 67 per cent of its users. Although research is ongoing on various aspects of SLT use and its effects, there is a need to identify the still under-researched areas in this field. This study was aimed at delineating the quantum of research on various topics of SLT, with intent to delineate research gaps for guiding future research priorities.Methods:Data about research in SLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Injectable steroids are clear fluids; their color and dose depend on the formulation of steroids used. It is commonly used in managing the longstanding oral lichen planus lesions and oral submucous fibrosis, but it has a localized side effect such as mucosal atrophy [21,22]. Hydrocortisone and triamcinolone are the commonest formulas used in local delivery with weekly injections reaching up to 11 injections [22,23].…”
Section: Corticosteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Injectable steroids are clear fluids; their color and dose depend on the formulation of steroids used. It is commonly used in managing the longstanding oral lichen planus lesions and oral submucous fibrosis, but it has a localized side effect such as mucosal atrophy [21,22]. Hydrocortisone and triamcinolone are the commonest formulas used in local delivery with weekly injections reaching up to 11 injections [22,23].…”
Section: Corticosteroidsmentioning
confidence: 99%
“…However, some investigators have suggested that the intralesional corticosteroid could be used as a new modality in the treatment, but cases of relapse with corticosteroid have been reported [24,25]. Great differences were detected in the used doses and the number of sessions according to the severity, extension, and the systemic condition of the patient [22,23,[26][27][28].…”
Section: Corticosteroidsmentioning
confidence: 99%